Ameliorative effects of curcumin against acute cadmium toxicity on male reproductive system in rats - Oguzturk, H.; Ciftci, O.; Aydin, M.; Timurkaan, N.; Beytur, A.; Yilmaz, F. (Wiley, 2012)
The aim of the present study was to investigate the ameliorative effect of curcumin (CMN) against acute cadmium chloride (CdCl2) toxicity on male reproductive system in rats. CdCl2 is known to be a heavy metal and potential environmental pollutant. For this purpose, 28 rats were equally divided into four groups; the first group was kept as control and given distilled water and corn oil as carrier. In second and third groups, CdCl2 and CMN were administered at the dose with 1 mg kg-1 day-1 and 100 mg kg-1 for 3 days respectively. CdCl2 and CMN were given together at the same doses in the fourth group. It was determined that acute CdCl2 exposure caused a significant reproductive damage via increased oxidative stress (increased TBARS levels and decreased SOD, CAT, GPx and GSH levels), histological alterations (necrosis, oedema etc.) and spermatological damage (decreased sperm motility and sperm concentration and increased abnormal sperm rate) in male rats. However, CMN treatment partially reversed these toxic effects of CdCl2 on the reproductive system. In conclusion, our results show that acute exposure of CdCl2 may lead to infertility, and CMN could prevent and reverse hazardous effects of CdCl2 to some degree. Thus, CMN may be useful for the prevention of CdCl2-induced reproductive damage.
Keywords: cadmium chloride; curcumin; oxidative stress; sperm parameters; testicular damage